2019
DOI: 10.3390/en12152896
|View full text |Cite
|
Sign up to set email alerts
|

Energy Use in Residential Buildings: Impact of Building Automation Control Systems on Energy Performance and Flexibility

Abstract: This work shows the results of a research activity aimed at characterizing the energy habits of Italian residential users. In detail, by the energy simulation of a buildings sample, the opportunity to implement a demand/response program (DR) has been investigated. Italian residential utilities are poorly electrified and flexible loads are low. The presence of an automation system is an essential requirement for participating in a DR program and, in addition, it can allow important reductions in energy consumpt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 58 publications
0
31
1
Order By: Relevance
“…The same building sample was used in other recent works of the authors so as to identify what are the flexible loads [39], to analyse the energy retrofitting effects on the potential of flexibility on the grid [40], and to evaluate the impact of building automation control systems on energy performance [41]; Section 3.1 provides a more extensive description of the sample characteristics.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The same building sample was used in other recent works of the authors so as to identify what are the flexible loads [39], to analyse the energy retrofitting effects on the potential of flexibility on the grid [40], and to evaluate the impact of building automation control systems on energy performance [41]; Section 3.1 provides a more extensive description of the sample characteristics.…”
Section: Methodsmentioning
confidence: 99%
“…The energy characterization reported in [39] shows that energy consumption for the inner space heating is on average equal to 43.5% of the total; energy consumption for cooling, in dwellings where the service is present, is on average 3.6%; the other services have a total incidence of 52.9% characterised by relative shares equal to 14.1% for DHW, 12.4% for cooking purpose, 5.6% for washing machines, and 4.1% for computer/Internet refrigeration 3.8%; thereafter the cleaning and ironing use represents only 3.5% while the care person lighting, audio/video, and the other equipment are equal to 2.9%, 2.7%, 1.8%, and 1.9%, respectively. For more information on the building sample characteristics and its energy characterization see [39][40][41].…”
Section: Dwellings Description and General Analysis On Consumptions Tmentioning
confidence: 99%
“…Coupling electrification and energy refurbishment, the actual integration of solar energy must be ensured from the pre-design to the operation phase [25]. Therefore, modelling and optimization should aim at cost-benefit analysis for renovation [26], together with the integration of Information & Communication Technologies (ICT) such as building automation [27].…”
Section: Introductionmentioning
confidence: 99%
“…Another study on school and offices buildings showed high energy saving potential [26], by introducing Demand Control Ventilation (DCV). Additionally, the implementation of Building Automation and Control (BACs) systems [27,28] can allow for HVAC operation with reduced airflow rates during the period with low occupancy and can therefore lead to relevant energy savings; in addition, BACs can also allow for combining the positive effects on energy consumption [29,30] of different ventilation systems with different control strategies. Indeed, one of the most usual solutions to reduce HVAC system energy consumption is currently to adopt smart control systems that might control airflow rate, supply air temperature and air humidity, and several other parameters.…”
Section: Introductionmentioning
confidence: 99%